2008
DOI: 10.1007/s00246-008-9325-x
|View full text |Cite
|
Sign up to set email alerts
|

Community Use of the Amplatzer Atrial Septal Defect Occluder: Results of the Multicenter MAGIC Atrial Septal Defect Study

Abstract: The objective of this study was to determine the initial safety and results of unrestricted multi-institution routine community use of the Amplatzer Septal Occluder (ASO) for atrial septal defect (ASD) closure. A multicenter, nonrandomized prospective study was performed in 13 pediatric cardiology centers from November 2004 to September 2007. Data were collected at the time of cardiac catheterization and 1 day postimplant. Four hundred seventy-eight patients underwent cardiac catheterization for ASO device clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 13 publications
10
33
0
4
Order By: Relevance
“…Our successful ASD device implant rate of 96.7% was similar to procedural success rates of 95.7% in the IMPACT Registry, 96% in the MAGIC report, 95% in the C3PO report, and 95.7% in the Amplatzer Septal Occluder FDA study (2,29,37,38). Major adverse events were observed in 1.3% in our study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our successful ASD device implant rate of 96.7% was similar to procedural success rates of 95.7% in the IMPACT Registry, 96% in the MAGIC report, 95% in the C3PO report, and 95.7% in the Amplatzer Septal Occluder FDA study (2,29,37,38). Major adverse events were observed in 1.3% in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Major adverse events were observed in 1.3% in our study. This rate compares with 1.2% in IMPACT patients, 1.1% in MAGIC patients, 4.7% in C3PO patients and 1.6% in the FDA study (2,29,37,38). As previously described, device embolization was successfully managed percutaneously in most cases (34).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Major and total adverse event rates were 1.6% and 7.2%, both significantly smaller than after surgical repair. The subsequent IMPACT Registry and MAGIC study reported similar success and complication rates [42,43]. ASO embolization is the most frequent adverse event as reported by the FDA Manufacturer and User Facility Device Experience database, accounting for 51% of events with a rate of 0.2-1.1%.…”
Section: Amplatzer Septal Occluder (Aso)mentioning
confidence: 89%
“…Fakat perkütan kapatma işleminde, geniş ya da multipl defekte sahip olan hastalar ile 1'den fazla occluder device kullanılan hastalarda rezidüel shunt oranı daha fazladır 8 .…”
Section: Discussionunclassified